A novel composition tunable combined cooling and power cycle using CO2-based binary zeotropic mixture. (15th September 2021) - Sun, Xiaocun; Shi, Lingfeng; Tian, Hua; Wang, Xuan; Zhang, Yonghao; Shu, Gequn
Highlights: A novel composition tuning combined cooling and power cycle is proposed. The performance of different cycle structures is compared. Better temperature match is achieved by composition adjustment. Proposed system obtains 5.18% increase in net power output. Abstract: Combined cooling and power cycle is a promising integrated system for its multi-function to simultaneously provide cooling and electricity. In order to alleviate temperature mismatch between working fluid and heat source/sink, combined cooling and power cycle coupled with zeotropic mixtures is put forward. Generally, a composition-fixed mixture cannot optimally match refrigeration sub-cycle and power sub-cycle meanwhile, as these two sub-cycles commonly have different performance regulation with various mixture composition. This research creatively proposes a novel composition tunable combined cooling and power cycle based on liquid separation condenser to realize different operation composition in two sub-cycles. CO2 mixture is condensed and separated to two streams with various concentrations through liquid separation condenser, one with high CO2 concentration, the other has low CO2 concentration. According to disparate flowing directions of two streams, two diverse structures are proposed in this study. Results demonstrate that the introduction of composition adjustment can substantially promote the comprehensive performance of the combined cycle. Taking a refrigeration truck as example, the new devised composition tunable combined cycle with initial composition of CO2 /R32 (0.500/0.500) can recover engine waste heat of the truck to generate power in power sub-cycle with low CO2 concentration (0.494), and provide required cooling capacity (5.43 kW) in refrigeration sub-cycle with high CO2 concentration (0.634). In addition to neutralizing compression work consumed in refrigeration sub-cycle, the new proposed system can extra generate 12.2 kW power, which is 5.18% higher than conventional composition-nonadjustable combined cycle. Besides, the total heat transfer areas of three systems are similar.